Survey for Cadmium Concentration in Liver, Kidney and Muscle of Slaughtered Sheep in Butcher Shops of Fallujah City, Iraq - Omar Fahad (مجلة الانبار للعلوم البيطرية)
Cadmium (Cd) is regarded as one of major the presence of hazardous substances in the environment, with a broad variety toxicity to organs and an extended half-life of removal. Cd exposure for farmed ruminants can come from industrial processing and intensive agricultural operations, which can pollute feed and water. It was noted that most of the wastes produced by nearby factories in Al Fallujah city are either strewn around the highways or use as landfills while the sewage is used for irrigation, while sheep graze on the edges of runways and other sites that might have been contaminated with hazardous materials. EF (enrichment factor) According to the findings, the concentration of Cd in the soils of Al Fallujah city was exceptionally high, and according to sediment content criteria, the soils in Fallujah city were contaminated with high concentrations of Cd, revealing the influence of human and industrial activity on Cd accumulation in the soil. Cadmium levels in liver, kidney and muscle from 216 samples for 72 slaughtered sheep in slaughterhouse at Al Fallujah city, Iraq during the period of October to December 2020 were analyzed. The values of Cadmium detected in sheep liver, kidney and muscle samples were 0.138± 0.020, 0.432 ± 0.090, and 0.037± 0.003 mg/kg, respectively which refer to high concentration of Cd in sheep viscera also This study demonstrates the need of assessing and monitoring cadmium and other hazardous metal levels in meals in order to create population-safe intake values.